2014
DOI: 10.1101/010629
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bayesian analyses of Yemeni mitochondrial genomes suggest multiple migration events with Africa and Western Eurasia

Abstract: Anatomically modern humans (AMHs) left Africa ~60,000 years ago, marking the first of multiple dispersal events by AMH between Africa and the Arabian Peninsula. The southern dispersal route (SDR) out of Africa (OOA) posits that early AMHs crossed the Bab el-Mandeb strait from the Horn of Africa into what is now Yemen and followed the coast of the Indian Ocean into eastern Eurasia. If AMHs followed the SDR and left modern descendants in situ, Yemeni populations should retain old autochthonous mitogenome lineage… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
(88 reference statements)
2
8
0
Order By: Relevance
“…Consistent with previous findings, our results also indicate that significant gene flow must have occurred between the Levantine and southern Arabian populations (Al‐Abri et al, ; Fernandes et al, ; Fernandes et al, ; Vyas et al, ; Vyas et al, ). This conclusion is supported by Vyas et al () based on ADMIXTURE analyses in which they found that two IACs made up most of the ancestry in these Levantine and southern Arabian populations.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous findings, our results also indicate that significant gene flow must have occurred between the Levantine and southern Arabian populations (Al‐Abri et al, ; Fernandes et al, ; Fernandes et al, ; Vyas et al, ; Vyas et al, ). This conclusion is supported by Vyas et al () based on ADMIXTURE analyses in which they found that two IACs made up most of the ancestry in these Levantine and southern Arabian populations.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous findings, our results also indicate that significant gene flow must have occurred between the Levantine and southern Arabian populations (Al-Abri et al, 2012; Fernandes et al, 2012; Fernandes et al, 2015; Vyas et al, 2017a; Vyas et al, 2016). Regardless of the origin of introgression in the Levant and southern Arabia or the relatedness of the populations in this regions, it would not be expected that selectively-neutral SNPs would maintain such similar frequencies in both regions (Tables S8, S10).…”
Section: Discussionsupporting
confidence: 92%
“…Concerning the less frequent L4, L5, and L6 clades, our L4b1a (Iv136) sequence from the Ivory Coast shares tip mutations 789, 7166 and 14935 with geographically close sequences (JQ044848, JQ045081) from Burkina Faso [72]. Likewise, the Arab L4a2 (AR1116) sequence is closely related to other African L4a2 sequences (EU092799, EU092800), and the L4b2a1 (AR197) isolate resulted identical to a sequence (KM986608) from Yemen [73]. From the analysis of partial sequences [53, 74], we can assure representatives of branches L4a1, L4a2 and L4b2 exist in Saudi Arabia.…”
Section: Resultsmentioning
confidence: 94%